Synchrotron X‐Ray Scanning Tunneling Microscopy: Synchrotron X‐Ray Scanning Tunneling Microscopy: Fingerprinting Near to Far Field Transitions on Cu(111) Induced by Synchrotron Radiation (Adv. Funct. Mater. 20/2013). (15th May 2013) - Rose, Volker; Wang, Kangkang; Chien, TeYu; Hiller, Jon; Rosenmann, Daniel; Freeland, John W.; Preissner, Curt; Hla, Saw‐Wai
<x xml:space="preserve">Abstract</x> On page 2646 Volker Rose and co‐workers present a smart tip for synchrotron X‐ray scanning tunneling microscopy that is entirely coated by an insulating oxide, except at the tip apex. The tip is only sensitive to X‐ray‐excited tunnel currents and not to photoejected electrons caused by classical photo emission, which would degrade the spatial resolution. The bright light in the image, coming in from the right, that hits the tip apex schematically represents the synchrotron beam during an experiment. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>